EVALUASI KEBIJAKAN SABILULUNGAN 1000 KAMPUNG KABUPATEN BANDUNG - Anjar Pratama Apriliyanto (Dialogue : Jurnal Ilmu Administrasi Publik, 2021)
Bandung Regency Government adapted the concept of developing an integrated planning area that utilizes a local base with the spirit of sabilulungan (Sundanese: gotong royong) which tries to integrate various development sectors in one activity called "Sabilulungan 1000 Kampung". After two years of implementing this concept where the villages have begun to be developed, it is necessary to see the level of success through an appropriate evaluation mechanism. This study tries to see how the evaluation of the implementation of this policy is through interviews with purposive sampling to the stakeholders of this program. The analytical method used is to utilize 5 evaluation criteria, namely effectiveness, adequacy, equity, responsiveness and accuracy which is used to see how the program has been running for these 2 years. Based on the analysis, it is seen that although programs and activities have shown a tourist attraction that is built and implemented according to the agreed time, the lack of monitoring and evaluation needs to be improved to get more equitable, precise, and sustainable results. More detailed action plans are needed. and operational and alternative funding schemes can help overcome existing barriers.